MENGEMAS PESONA HERBAL DALAM PEMBELAJARAN IPA SEBAGAI UPAYA MENUMBUHKAN KESADARAN LINGKUNGAN - Asri Widowati (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2016)
Herbs are one of the natural wealth of Indonesia that has been used for generations. But unfortunately, the prestige is so legendary that the less there is a follow up. Not many young people who know the herbs and usefulness. This is due to the progress of society with owned facilities have come to globalizing mainstrem life in the 21st century, including the handling of health problems. Beauty of herbs need to be preserved because the longer it is already fading, and fear that the future will be lost. It can be anticipated by utilizing the "Beauty of Herbs" in science lessons. Learning science can do to help raise environmental awareness education to be able to face the challenges of the environmental crisis in the 21st century with "linking knowledge to action".Keywords: beauty of herbs, learning science, environment awareness.